Pengaruh Metode Bermain Peran terhadap Kreativitas Anak Usia Dini di PAUD - Nurul Aini Mm. Sodik; Juwita Moodumbi; Isnawati Daintaw; Sri Mulyani (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This research aims to determine the influence of the role-playing method on the creativity of early childhood at Miftahul Jannah TPA. Creativity as an important aspect of development needs to be stimulated from an early age through activities that are fun and meaningful for children. This research uses a quantitative approach with a pre-experimental design type one group pretest-posttest design, where researchers measure creativity before and after role-playing treatment. The research results show that the role playing method has a positive influence on the development of children's creativity. This can be seen from the increase in scores on several indicators of creativity, such as the ability to generate ideas, elaboration and concentration. The elaboration indicator received the highest score in the very good category, indicating that children were able to add details and enrich the storyline during role play. However, the indicators of flexibility and authenticity are still in the poor category and require further stimulation. Overall, an average creativity score of 54 was obtained, which shows that role playing is effective in stimulating children's creativity. These findings emphasize that role-playing methods need to be applied variedly and continuously in learning to optimize the creativity of early childhood.